Uji Penyembuhan Luka Bakar Gel Enzim Bromelin Menggunakan Carbopol 940 Secara In Vivo - Nur Ain Thomas; Muhammad Taupik; Endah Nurrohwinta Djuwarno; Nabila Novreini Djunaidi; Dizky Ramadani Putri Papeo (State University of Gorontalo, 2023)
Bromelain is a proteolytic enzyme or natural protease found in tissues, including the stem, fruit, and leaves of pineapple (Ananas comosus var. comosus) and other plant species of the Bromeliaceae family. Bromelain is known as an efficient debdriding agent because it is beneficial inÂ burn healing and tissue regeneration. This research aims to determine the effectiveness of bromelain enzyme for burns wounds in rabbits (Oryctolagus cuniculus). This research began with the optimization of carbopol 940 base preparations with variations in concentration, namely Formula 1 (F1) for 0,5%, Formula 2 (F2) for 1%, and Formula 3 (F3) for 1,5%. The evaluation of the gel formulation includes an organoleptic test, homogeneity test, pH test, viscosity test, adhesive force test, and spreadability test. The evaluation result indicates the base concentration in Formula 1 (F1) at 0,5% has met the requirements for a gel preparation. Formula 1 (F1) for 0,5, then combined with varying concentration of bromelain, namely Formula 1A (0,1%), Formula 1B (0,5%), and Formula 1C (1%). The gel formulation wa re-evaluated, including an organoleptic test, homogeneity test, pH test, viscosity test, adhesion test, spreadability test, irritation test, and in vivo test. In vivo effectiveness testing and irritation testing were conducted on five treatment groups, namely a positive control group (BioplacentonÂ®), Formula 1A (0,1%), Formula 1B (0,5%), Formula 1C (1%), and a group without treatment, then observed for 15 days. The observation data were processed using the One Way ANOVA test. Based on the results of the irritation test, Formula 1A (0,1%). Formula 1B (0,5%) and Formula 1C (1%) did not cause skin irritation. In the in vivo test, Formula 1C (1%) indicated the fastest recovery compared to other treatment groups, as evidenced by the decrease in wound diameter and visual observation, where the wound had started to close completely on day 15 of observation.